The Fragmented Family Theme In Film - Wei, Dickson Ng Chia (Universiti Malaysia Sarawak(UNIMAS), 2018)
The purpose of this research is to study about the fragmented family theme in film. For this thesis, the research is conducted mainly based on the film directed by Malaysian Director Ho Yu Hang, which is “Rain Dogs”. There are very few researchers who are conducting researches on fragmented family theme in film, especially on Malaysian films. There are many famous film directors who made films based on fragmented family theme, including the renowned film director from Hollywood, Steven Spielberg, and the films actually received a good review from public. With that, the researcher will be focusing on how a film of fragmented family theme is made according to the data collected in my research methodology. Therefore, it is crucial for the researcher to conduct this research about fragmented family theme in film so that the outcome of the thesis will bring contributions in the Malaysian film industry.